The Expansion of Pedagogical Alignment: A Step for the Learning Success - Justino, Júlia (2020)
The adaptation of higher education institutions to the changing needs of employers and society demands critical and creative ability in the elaboration of new curricula. The implementation of these new curricula requires a change in methodology to the learner-centered approach that is not easy at first and requires a deeper reflective and analytical attitude from the teacher. How it starts and how should be applied is a recurring issue at conferences and is the subject of this paper. The first step consists of building the training structure to be implemented, been usual to build a structure which supports contents, learning outcomes and assessment methodology. But this is not sufficiently comprehensive to provide guidance and reflection to the teacher about the learning activities to be implemented nor the learning itself, even with the support of an IT tool to maintain the focus and establish the development phases of the pedagogical structure. The new feature presented in this paper is the expansion of the training structure to all educational elements needed for the implementation of the student-centered approach. An example is given within the context of a course unit of a short-cycle tertiary educational programme (2 years – 180 ECTS), providing the syllabus planning, the learning outcomes setting, linking them with their ground level of cognition, the teaching-learning activities setting for each specific content, the resources to students allocation and/or creation, structuring them on an IT platform, the pedagogical strategies setting and the evaluation method definition. This planning allows to structure the whole teaching-learning process of the course unit, considering the available timeframe, the application environment or context, the students’ competences to exercise and the teacher’s pedagogical skills.